Flow regime analysis of the pressure build-up during CO2 injection in saturated porous rock formations - Sarris, Ernestos; Gravanis, Elias (My University, 2019)
In this work, we are concerned with the theoretical and numerical analysis of the pressure build-up on the cap of an aquifer during CO2 injection in saturated porous rock formations in all flow regimes of the problem. The latter are specific regions of the parameter space of the plume flow, defined by the CO2-to-brine relative mobility and the buoyancy parameter (injection pressure to buoyancy pressure scale ratio). In addition to the known asymptotic self-similar solutions for low buoyancy, we introduce two novel ones for the high buoyancy regimes via power series solutions of asymptotic self-similarity equations. The explicit results for the peak value of pressure on the cap, which arises in the vicinity of the well, are derived and discussed for all flow regimes. The analytical results derived in this work are applied for the purpose of cap integrity considerations in six test cases of CO2 geological storage from the PCOR partnership, most of which correspond to high buoyancy conditions. The validity of the self-similar solutions (late time asymptotics) is verified with CFD numerical simulations performed with the software Ansys-Fluent. The result is that the self-similar solutions and the associated pressure estimations are valid in typical injection durations of interest, even for early times.
Keywords: Caprock stability; CO2 sequestration; Flow regimes; Gravity segregation; Multiphase flow; Porous media; Pressure build-up; Saline aquifer; Self-similar; VOF method